Robin Lee. (1st June 2020) - Griffiths, Ian; Holmes, Peter; Sullivan, Martin; Wright, Norman
Abstract : A respected and popular academic at University of Glasgow Veterinary School, he played a key role in the development of investigative radiology of small animals.